Rectal Culture-Based Versus Empirical Antibiotic Prophylaxis to Prevent Infectious Complications in Men Undergoing Transrectal Prostate Biopsy: A Randomized, Nonblinded Multicenter Trial. (24th November 2022) - Tops, Sofie C M; Kolwijck, Eva; Koldewijn, Evert L; Somford, Diederik M; Delaere, Filip J M; van Leeuwen, Menno A; Breeuwsma, Anthonius J; de Vocht, Thijn F; Broos, Hans J H P; Schipper, Rob A; Steffens, Martijn G; Teerenstra, Steven; et al.
Abstract: Background: An increase in infections after transrectal prostate biopsy (PB), related to an increasing number of patients with ciprofloxacin-resistant rectal flora, necessitates the exploration of alternatives for the traditionally used empirical prophylaxis of ciprofloxacin. We compared infectious complication rates after transrectal PB using empirical ciprofloxacin prophylaxis versus culture-based prophylaxis. Methods: In this nonblinded, randomized trial, between 4 April 2018 and 30 July 2021, we enrolled 1538 patients from 11 Dutch hospitals undergoing transrectal PB. After rectal swab collection, patients were randomized 1:1 to receive empirical prophylaxis with oral ciprofloxacin (control group [CG]) or culture-based prophylaxis (intervention group [IG]). Primary outcome was any infectious complication within 7 days after biopsy. Secondary outcomes were infectious complications within 30 days, and bacteremia and bacteriuria within 7 and 30 days postbiopsy. For primary outcome analysis, the χ 2 test stratified for hospitals was used. Trial registration number: NCT03228108. Results: Data from 1288 patients (83.7%) were available for analysis (CG, 652; IG, 636). Infection rates within 7 days postbiopsy were 4.3% (n = 28) (CG) and 2.5% (n = 16) (IG) ( P value = .08; reduction: −1.8%; 95% confidence interval, −.004 to .040). Ciprofloxacin-resistant bacteria were detected in 15.2% (n = 1288). In the CG, the presence of ciprofloxacin-resistant rectal flora resulted in a 6.2-fold higher risk of early postbiopsy infection. Conclusions: Our study supports the use of culture-based prophylaxis to reduce infectious complications after transrectal PB. Despite adequate prophylaxis, postbiopsy infections can still occur. Therefore, culture-based prophylaxis must be weighed against other strategies that could reduce postbiopsy infections. Clinical Trials Registration . NCT03228108. Abstract : Our study supports using culture-based prophylaxis to reduce infectious complications after transrectal prostate biopsy, especially with regard to the early, more severe infections. Despite adequate prophylaxis, patients can still develop postbiopsy infection; therefore, other strategies need to be explored as well.